Spectacle. Book one - Gedris, Megan Rose, 1986- (Oni Press, 2018)
Anna is working as a psychic at the Samson Brothers Circus with her twin sister, Kat, when Kat is murdered and comes back as a ghost who inhabits Anna's body. The two set out to find Kat's killer amidst circus secrets and paranormal happenings.